2014
DOI: 10.1063/1.4904019
|View full text |Cite
|
Sign up to set email alerts
|

High electrostrictive coefficient Q33 in lead-free Ba(Zr0.2Ti0.8)O3-x(Ba0.7Ca0.3)TiO3 piezoelectric ceramics

Abstract: In this study, the electrostrictive effect in Ba(Zr0.2Ti0.8)O3-x(Ba0.7Ca0.3)TiO3 (BZT-xBCT, x = 0.4, 0.5, and 0.6) ceramics was investigated to gain understanding of their high piezoelectric activity. The electrostrictive coefficient Q33 of the BZT-xBCT ceramics was observed to be around 0.04 m4/C2, twice that reported for Pb(Zr,Ti)O3-based ceramics. The Q33 was found to be quite stable with respect to temperature and composition for the BZT-xBCT ceramics. The addition of Fe3+ dopant to the ceramics greatly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(44 citation statements)
references
References 17 publications
4
40
0
Order By: Relevance
“…The strain for a 0.5BZT-0.5BCT ceramic can reach 0.05% in an electric field of 500 kV/mm [14], which is even larger than PZT-5H at the same electric field condition. Moreover, Bowman's group and other groups even reported a larger strain level at a near-MPB composition [59][60][61], which makes BZT-BCT ceramic a promising material for actuator application [62][63][64][65]. Besides piezoelectric coefficients, other parameters, such as maximum polarization, remnant polarization, dielectric permittivity etc.…”
Section: Ba(zr02ti08)o3-(ba07ca03)tio3mentioning
confidence: 99%
“…The strain for a 0.5BZT-0.5BCT ceramic can reach 0.05% in an electric field of 500 kV/mm [14], which is even larger than PZT-5H at the same electric field condition. Moreover, Bowman's group and other groups even reported a larger strain level at a near-MPB composition [59][60][61], which makes BZT-BCT ceramic a promising material for actuator application [62][63][64][65]. Besides piezoelectric coefficients, other parameters, such as maximum polarization, remnant polarization, dielectric permittivity etc.…”
Section: Ba(zr02ti08)o3-(ba07ca03)tio3mentioning
confidence: 99%
“…The values of 33 = 0.04 m 4 /C 2 for BZT-BCT were reported and are relatively insensitive to variations of composition and temperature. 350 This suggests that is not the parameter determining differences in electromechanical properties. Therefore, as a first approximation, variations in the values are neglected.…”
Section: Equation 59mentioning
confidence: 99%
“…342 Moreover, the O to T PPB is more elastic than the R to T PPB ( Figure 3.3 (c)), and displays similar elasticity as the convergence region. 318,341,349 Li et al 350 reported that the electrostrictive coefficients of BZT-BCT are ~ 0.04 m 4 /C 2 and remain relatively constant with composition and temperature. It was demonstrated that switching determines to a great extent small 323 and large 329 signal properties.…”
Section: Electromechanical Propertiesmentioning
confidence: 99%
“…For instance, it was suggested that the large piezoelectric coefficient of the lead-free ceramic system BZT-BCT 6,7 is originated from its large electrostriction coefficients. It is obvious that accurately obtaining electrostriction coefficient is a key step in such research.…”
Section: Introductionmentioning
confidence: 99%